Vermicompost leachates enhance morpho-physiological properties in Pelargonium sidoides DC - McMaster Vambe; Karishma Singh; Roger M. Coopoosamy; Kuben Naidoo; Rebecca Zengeni (AOSIS, 2024)
Background: Pelargonium sidoides (Geraniaceae family) is extensively used in African folk medicine to manage several diseases including gonorrhoea, tuberculosis, gastro-intestinal, hepatic and menstrual disorders. The plant's parts and efficacious extract-based pharmaceutical products are sold in several local and international markets. However, the growing demand for the herb has resulted in overexploitation of its wild populations, prompting an urgent need to develop sustainable production and conservation strategies. Aim: The present study investigated the effects of vermicompost leachate (VCL) on morpho-physiological properties of greenhouse-grown P. sidoides. Setting: Pelargonium sidoides seeds were supplied by the Mountain Herb Estate (Pretoria, South Africa), and all experiments were conducted at the University of KwaZulu-Natal, Pietermaritzburg, South Africa. Methods: Six-week-old seedlings of the plant were watered regularly and subjected to 50 mL (soil drench) of VCL (1:5, 1:10 or 1:20; VCL: water, v/v dilution) once a week. After 8 weeks, the seedlings were harvested, and morphological parameters, antioxidant activity, phytochemical and photosynthetic pigment content determined. Results: The VCL (1:5, 1:10 and 1:20; VCL: water) induced a significant (p ≤ 0.05) increase in the concentration of phenolic compounds, photosynthetic pigments, canopy size, leaf area, number of tubers, fresh and dry weights in treatments compared to the control. The antioxidant activity also increased by 7% - 27 % in treatments compared to the control. Conclusions: The study showed that VCL improves the yield and quality of P. sidoides. Contribution: The use of VLC could, therefore, potentially help in the conservation and large-scale production of the herb.